The disreputable history of Frankie Landau-Banks : a novel - Lockhart, E. (Hyperion, 2008)
Sophomore Frankie starts dating senior Matthew Livingston, but when he refuses to talk about the all-male secret society that he and his friends belong to, Frankie infiltrates the society in order to enliven their mediocre pranks.